Does Ring Current Heating Generate the Observed O+ Shell?. Issue 14 (16th July 2020) - Krall, J.; Huba, J. D.; Fok, M.‐C.
Abstract: The Naval Research Laboratory (NRL) Sami3 is Also a Model of the Ionosphere (SAMI3) ionosphere/plasmasphere code is used to examine the effect of ring current heating during a storm. With a ring current heating function added to SAMI3, a cold thermal (<1 eV) oxygen ion outflow is produced, with O + density and location similar to observations of the so‐called "oxygen torus." The ring current heating function is based on a Comprehensive Inner Magnetosphere‐Ionosphere (CIMI) model simulation of the 7 October 2015 storm. We find that the ring current can heat plasmasphere electrons, subsequently heating plasmasphere H +, and ionosphere O + . The resulting O + outflows resemble observed O + enhancements in the inner magnetosphere. Plain Language Summary: The near‐Earth environment includes relatively low‐energy "cold" ions with temperatures less than 10 5 K (8.6 eV) and much higher energy ions. We specifically consider thecold plasmasphere, the magnetically contained extension of the ionosphere into space, and the ring current, a high‐energy (1–100 keV) population of O + and H + ions generated during a geomagnetic storm. We numerically model the interaction between these populations in search of an explanation for the cold oxygen ions that are observed near the edge of the plasmasphere. Results suggest that the ring current heats plasmasphere electrons, plasmasphere H +, and ionosphere O + . The heated O + flows upward along the geomagnetic field, forming the "oxygen torus" that has been observed by numerous spacecraft. Key Points: Simulated ring current heating produces an outflow of "cold" (<1 eV) oxygen ions into the magnetosphere Model oxygen ion densities and positions are similar to observations of the so‐called "oxygen torus" Model oxygen ion enhancements resemble a partial toroidal shell that extends outwards along the geomagnetic field